h.hofstede (h.hofstede@hogeland.nl)

1. a. x-2 x5 = x-3
  b. x/x-4  =  x3 x4 = x7
  c. 1/x6 1/x-4 = x-6 x4 = x-2
  d. x4   1/x7 = x4x-7 = x-3
  e. x3 1/x = x3x-1 = x2
  f. x x6 x-2 = x1 - 6 - 2 = x-7
  g. x5 (x4)-3 = x5 x-12 = x-7
  h. (x-3)2 1/x-4 = x-6 x4 = x-2 
  i. (x/x)4 = (x1x-3)4 = (x-2)4 = x-8
     
2. a. 6a-4 b3 = 6b/a4
  b. 1/5 p-2 = 1/5p2
  c. (5p)-4 1/p = 1/54p4 1/p  =  1/625p5
  d. (3/4)-2 = 3-/4-2 = 4/32 = 16/9
  e. (1/x-3 )4 = 1/x-12x12
  f. (x/x)4 = (1/x2 )4 = 1/x8
     
3. a.
    =  64x4 (2x2)-5
=  64x4 2-5 x-10
= 2x-6
       
  b.
    = 40x-5 4-1 x-4 x7
= 10x-5 - 4 + 7
= 10x-2
       
  c.
    = 3x4 10-1 x-2 x-3 20x-5
= 6x4 - 2 - 3 - 5
= 6x-6
       
       

h.hofstede (h.hofstede@hogeland.nl)